2008
DOI: 10.1021/jp7103243
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fickian Water Vapor Sorption Dynamics by Nafion Membranes

Abstract: Dynamics of water absorption from a saturated vapor and water desorption into dry air for Nafion 1100 EW ionomers have been measured for film thicknesses between 51 and 606 microm and at temperatures ranging from 30 to 90 degrees C. Water absorption and desorption exhibit two distinct non-Fickian characteristics: (1) desorption is 10 times faster than absorption and (2) the normalized mass change does not collapse to a single master curve when plotted against time normalized by membrane thickness squared, t/l2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
206
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(237 citation statements)
references
References 40 publications
(137 reference statements)
26
206
3
Order By: Relevance
“…They further explain that this apparent constraint relaxes with increasing temperature and water content. Similarly, in a study by Satterfield and Benziger [75] on the water sorption dynamics of predried PFSA membranes, the rate of water sorption was found to increase with increasing temperature, which they attributed to the relaxation of the polymer matrix. Therefore, there is experimental evidence to suggest that the water uptake is influenced by the temperature effect on the behavior of the polymer matrix.…”
Section: Effect Of Temperaturementioning
confidence: 71%
“…They further explain that this apparent constraint relaxes with increasing temperature and water content. Similarly, in a study by Satterfield and Benziger [75] on the water sorption dynamics of predried PFSA membranes, the rate of water sorption was found to increase with increasing temperature, which they attributed to the relaxation of the polymer matrix. Therefore, there is experimental evidence to suggest that the water uptake is influenced by the temperature effect on the behavior of the polymer matrix.…”
Section: Effect Of Temperaturementioning
confidence: 71%
“…For example, it uses values for interfacial mass-transfer coefficients that are large and thus do not represent a significant resistance for transport to/from the vapor phase, counter to some recent experimental studies [20,21]. Making this value smaller would result in larger water hold-up in the anode and perhaps a drier membrane, which could explain why the profile at the anode MPL is wrong at 40°C.…”
Section: Resultsmentioning
confidence: 98%
“…The interfacial resistance was shown to be the limiting step for water transport in thinner membranes (less than 25 µm) at lower temperatures (25 o C) 52,54 and at high 5 relative humidity. 55 Interestingly, Zhao et al 55 reported RH-independent interfacial resistance whereas Kienitz et al, 56 reported a decrease in mass-transport coefficient with increasing RH.…”
Section: -55mentioning
confidence: 97%